ДИФФЕРЕНЦИАЛЬНАЯ ДИАГНОСТИКА ГИПЕРТЕРМИЙ ПРИ НЕИНФЕКЦИОННОЙ ПАТОЛОГИИ. ЧАСТЬ 1 - А. Н. Смирнов; Е. П. Погорельская; С. А. Васильев (Архивъ внутренней медицины)
The article discusses the questions of pathogenesis, clinic, diagnosis and differential diagnosis of fever, caused by visceral non-infectious pathology, including tumors, haemopathies, rheumatic diseases ,imunocomplex and neuroendocrine abnormalities. Are some of the algorithms of diagnostics at the hyperthermia for General practitioners, including assessment of haematologia.Окончание статьи читайте в № 5 журнала «Архивъ внутренней медицины».